BUMDes Management Strategy in Improving Community Economic Welfare: (Case Study of East Sukadamai Village, Langkat Regency) - Luis, Muhammad; Yafiz, Muhammad; Jannah, Nurul (Yayasan Sinergi Kawula Muda, 2024)
This research aims to find BUMDes management strategies to improve the economy of village communities. The method used is a qualitative method by conducting field interviews, then the results are analyzed using the SWOT method. The results show that in the SWOT analysis BUMDes has not carried out its management optimally, and has not been able to improve the economic welfare of the village community, thus the impact of the establishment of BUMDes has not been felt by the community in Suka Damai Timur Village. The results of the SWOT matrix analysis, namely strategies (S-O), (W-O), (S-T), (W-T), found that BUMDes must implement several strategies to improve the economy of village communities, namely by conducting strategic business partnerships, Diversifying Products and Services, Carrying out Integrated Livestock Development, Opening Livestock and Technology Training Centers, Improving Marketing and Distribution Networks, Utilizing technology as a means of promotion, Improving facilities and infrastructure, Increasing Funding and Facilities, Technology Training on Social Media, Proposing Pilot Projects to Government and Investors, Minimizing Competition, Utilizing Strategic Locations to Attract More Customers, Developing Sustainability and Risk Management Programs, Improving Services and Community Involvement, Training and Increasing Capacity, Diversifying Revenue Sources, Increasing Transparency and Accountability. By implementing these strategies, it is hoped that BUMDes will be able to drive the economy of Sukadamai Timur village, so that BUMDes can contribute to improving the economy of the people in the village. So that BUMDes can achieve its goals that have been regulated by the government in accordance with the function of creating the BUMDes.